Dietary interventions for functional abdominal pain disorders in children: a systematic review and meta-analysis. (3rd April 2022) - de Bruijn, Clara MA; Rexwinkel, Robyn; Gordon, Morris; Sinopoulou, Vassiliki; Benninga, Marc A; Tabbers, Merit M
ABSTRACT: Background: Functional abdominal pain disorders (FAPDs) are common among children and are associated with decreased quality of life and school attendance. Several dietary interventions have been suggested to improve symptoms of FAPDs. This systematic review assessed the efficacy and safety of dietary interventions for pediatric FAPDs. Design and methods: Electronic databases were searched (inception–October 2021). Systematic reviews or RCTs were included if children (4–18 years) with FAPDs were treated with dietary interventions and compared to placebo, no diet or any other diet. Data extraction and assessment of quality of evidence based on GRADE system was independently performed by two review authors. Outcomes were treatment success, pain intensity and frequency, and withdrawal due to adverse events. Results: Twelve articles were included, representing data of 819 pediatric FAPD patients. Trials investigating fibers, FODMAP diet, fructans, fructose-restricted diet, prebiotic (inulin), serum-derived bovine immunoglobulin, and vitamin D supplementation were included. We found very low-certainty evidence that the use of fibers leads to higher treatment success (NNT = 5). Conclusion: Based on current evidence, the use of fibers can be discussed in daily practice. High-quality intervention trials are highly needed to investigate if other dietary interventions are effective in the treatment of pediatric FAPD.